Diseño efectivo de clases a través del manejo de aula - Lozano Rosero, Pablo César (Universidad Santiago de Cali, 2017)
To design effectively a class is essential to obtain the expected result of the teaching-learning process. In the design, important factors such as the ma-nagement of the class, the learning environments, the interest, motivation of the students and the leadership that both teachers and students should have to assimilate the conditions of the school in the 21st century. Leadership consists in creating, feeding and developing the capacity of teachers and students to get involved in a high-level learning and to think about their own learning practice. Elmore, R. (2010).